KAJIAN BIBLIOMETRIK TERHADAP ARTIKEL BIDANG TEKNOLOGI MINYAK DAN GAS BUMI DI INDONESIA (BIBLIOMETRIC STUDY OF THE OIL AND GAS TECHNOLOGY FIELD IN INDONESIA) - Himawanto, Himawanto (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2015)
Energy problems is still a big topic and be a tough challenge in Indonesia so it is important to present a strategic move to seek a solution through research and study. Lembaran Publikasi Minyak dan Gas Bumi, Scientific Contribution Oil and Gas, dan Jurnal Teknologi Minyak dan Gas Bumi is the tool used by researchers to compile the results of innovative research and studies. To know the charge articles, authorship patterns, characteristics, and productivity of researchers used bibliometric study. During the period 2011-2013 as many as 91 researchers produced 159 articles. Most are the result of research on the exploitation of the technology by 71 articles (44.65%), while the other main focus of exploration technologies such as achieving 17 articles (10.69%). Coverage includes a research collaboration between countries, involving two to four researchers over the level of collaboration reached 61.01%. Overall oil and gas research activities dominated R & D institutions, universities and businesses.